2013
DOI: 10.3389/fimmu.2013.00373
|View full text |Cite
|
Sign up to set email alerts
|

IgM Repertoire Biodiversity is Reduced in HIV-1 Infection and Systemic Lupus Erythematosus

Abstract: Background: HIV-1 infection or systemic lupus erythematosus (SLE) disrupt B cell homeostasis, reduce memory B cells, and impair function of IgG and IgM antibodies.Objective: To determine how disturbances in B cell populations producing polyclonal antibodies relate to the IgM repertoire, the IgM transcriptome in health and disease was explored at the complementarity determining region 3 (CDRH3) sequence level.Methods: 454-deep pyrosequencing in combination with a novel analysis pipeline was applied to define po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 100 publications
1
15
0
1
Order By: Relevance
“…In SLE, naïve B cells may be initially hyper-activated and produce higher levels of anti-dsDNA antibodies but this eventually leads to necroptosis (33), which would explain the lower B cell numbers in our study. Furthermore, in comparison to healthy controls, patients with SLE have lower frequency of BCR sequences with somatic hypermutations (SHM) (34). In animal models, the reduction in naïve B cells promotes Cryptococcus dissemination (35) and the lower biodiversity of BCR sequences with SHM in patients with SLE (34) may diminish the B cell repertoire to combat infections.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In SLE, naïve B cells may be initially hyper-activated and produce higher levels of anti-dsDNA antibodies but this eventually leads to necroptosis (33), which would explain the lower B cell numbers in our study. Furthermore, in comparison to healthy controls, patients with SLE have lower frequency of BCR sequences with somatic hypermutations (SHM) (34). In animal models, the reduction in naïve B cells promotes Cryptococcus dissemination (35) and the lower biodiversity of BCR sequences with SHM in patients with SLE (34) may diminish the B cell repertoire to combat infections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in comparison to healthy controls, patients with SLE have lower frequency of BCR sequences with somatic hypermutations (SHM) (34). In animal models, the reduction in naïve B cells promotes Cryptococcus dissemination (35) and the lower biodiversity of BCR sequences with SHM in patients with SLE (34) may diminish the B cell repertoire to combat infections. Also, the lower pool of naïve B cells could lead to less class-switched memory B cells, which are known to be fundamental in the prevention of infections in other clinical conditions (36).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, on the basis of alterations of the human B-cell repertoire after HIV and influenza infection 48 49 , we assessed the effects of Env vaccination and SHIV AD8 infection on V H gene usage. Sundling et al 50 reported relative similarities in V H gene usage between Env-specific and total memory B cells after vaccination, a finding confirmed here.…”
Section: Discussionmentioning
confidence: 99%
“…High-throughput sequencing of BCR repertoires from peripheral blood has shown that patients with SLE exhibit increased B-cell clonality compared with heathy individuals. 46,47 This is characterized by polyclonal (multiple) Bcell expansions. 36 This is possibly secondary to increased numbers of plasmablasts.…”
Section: Clonality and Cdr3 Region Composition Of Antibodies In Slementioning
confidence: 99%